Solution of Fractional Kinetic Equation with Laplace and Fourier Transform (Global Journal of Science Frontier Research, 2012)
In earlier paper Saxena et al.(2002,2003)[18],[19] derived the solutions of a number of fractional kinetic equations in terms of generalized Mittage-Leffler functions which extended the work of Haubold and Mathai (2000)[5].The objects of present paper is to investigate the solution of fractional diffusion equation involving Mittag-Leffler functions. The method involves simultaneous application of Laplace and Fourier transforms with time and space variable respectively. The results obtained are in a form of H-function.
Keywords: Mittage-Leffler function; Fractional Kinetic Equation; Laplace Transform; Fourier Transform amd H-functions